2023
DOI: 10.3389/fonc.2023.1062424
|View full text |Cite
|
Sign up to set email alerts
|

A new intronic quantitative PCR method led to the discovery of transformation from human ascites to murine malignancy in a mouse model

Abstract: PurposeTo establish a fast and accurate detection method for interspecies contaminations in the patient-derived xenograft (PDX) models and cell lines, and to elucidate possible mechanisms if interspecies oncogenic transformation is detected.MethodsA fast and highly sensitive intronic qPCR method detecting Gapdh intronic genomic copies was developed to quantify if cells were human or murine or a mixture. By this method, we documented that murine stromal cells were abundant in the PDXs; we also authenticated our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…In our study of human ascites to murine stromal oncogenic transformation, no humanmurine cell fusions were found, but a sole human somatic mutation, TP53-D281E, was found in the GA0825-PDX model by WES analysis [31]. This mutation may have played a role in oncogenic transformation, as it is adjacent to R282, one of the most common amino acid alterations in TP53 mutations that fail to bind to DNA, specifically, at the TP53 DNA regulatory sequence [44].…”
Section: The Mechanism Of How Human Cancer Cells Transformed Murine S...mentioning
confidence: 67%
See 4 more Smart Citations
“…In our study of human ascites to murine stromal oncogenic transformation, no humanmurine cell fusions were found, but a sole human somatic mutation, TP53-D281E, was found in the GA0825-PDX model by WES analysis [31]. This mutation may have played a role in oncogenic transformation, as it is adjacent to R282, one of the most common amino acid alterations in TP53 mutations that fail to bind to DNA, specifically, at the TP53 DNA regulatory sequence [44].…”
Section: The Mechanism Of How Human Cancer Cells Transformed Murine S...mentioning
confidence: 67%
“…These observations indicated that human prostate tumors were transformed by human tumor cells into mouse oncogenic cells. We (Jin et al, 2023) reported that human ascitic cells (GA0825) from a GAC patient transformed murine stromal cells into a malignant tumorigenic murine P0825 cell line, in a PDX model, in a time-progressive manner [31]. Human-host oncogenic transformation in the PDXs is summarized in Figure 4A,B.…”
Section: Human-to-host Oncogenic Transformation and Murine Contaminationmentioning
confidence: 97%
See 3 more Smart Citations